Sorghum as food in the semi-arid tropics: studies in the dryland communities of Andhra Pradesh, India - Pushpamma, P. (IDRC OttawaCA, 1993)
Explains the need to increase the use of sorghum and describes the current food system using sorghum. Looks at improved varieties, marketing ,storage, current processing and utilization methods, and the nutritional status of sorghum foods.